Water Quality and Nutrient Management Extension Programs in Ohio. (29th January 2016) - Londo, Andrew J.; LaBarge, Greg; Watters, Harold; Culman, Steve; Rose, Mary Ann; Hall, Peggy; Arnold, Glen; Custer, Sam; Richer, Eric; Noggle, Sarah; Penrose, Chris
Abstract: Extension has a long history of conducting educational programs for agricultural producers on a wide array of issues, including water quality. In Ohio, the focus of these educational efforts has grown to include best management practices for nutrient management. The need for education in nutrient management began in earnest in the 1970s due to the presence of harmful algal blooms (HAB) in the Western Lake Erie Basin. International actions taken during that time all but eliminated the HABs from the lake until they made a resurgence in the 1990s. Twenty years later, the HAB threat in Lake Erie is still present and has major implications for commerce, tourism, and human and environmental health. The HAB threat has spurred outcries from the general public, resulting in the creation of new laws by the Ohio Legislature, and an expanded and enhanced focus area for Ohio State University Extension (OSUE) programming. In this paper, we describe the conditions that have led to the development of the HAB in Lake Erie, the legislative action that has been taken in attempts to curb the problem, and the educational programs developed by OSUE in partnership with state agencies, non‐government organizations, and other interested parties to address these water quality issues with Ohio agricultural producers and the general public.